2017
DOI: 10.18632/oncotarget.19937
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomogram based on lncRNA ZFAS1 for predicting survival in lymph node-negative esophageal squamous cell carcinoma patients

Abstract: BackgroundThere is increasing evidence of a relationship between long non-coding RNA (lncRNA) and cancer. This study aimed to examine the prognostic value of the lncRNA ZFAS1 in esophageal squamous cell carcinoma (ESCC).ResultsThe results showed that ZFAS1 expression was significantly higher in ESCC tissues compared with the corresponding adjacent normal tissues (P < 0.001). ESCC patients with high ZFAS1 expression had a poor overall survival (OS). Histological grade, T stage and ZFAS1 expression were integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Furthermore, Zhou et al [ 27 ] and Pan et al [ 28 ] similarly showed that circulating/serum ZFAS1 levels were significantly associated with clinical stage (TNM stage), lymph node metastasis (N classification), and distant metastasis. In addition, the analogous clinical significance of ZFAS1 was also reported in esophageal squamous cell carcinoma [ 30 ] and ovarian cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Furthermore, Zhou et al [ 27 ] and Pan et al [ 28 ] similarly showed that circulating/serum ZFAS1 levels were significantly associated with clinical stage (TNM stage), lymph node metastasis (N classification), and distant metastasis. In addition, the analogous clinical significance of ZFAS1 was also reported in esophageal squamous cell carcinoma [ 30 ] and ovarian cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 52%
“…Subsequently, Fan et al [ 18 ] also showed ZFAS1 expression was down-regulated in breast cancer cell lines, and acted as a tumor suppressor in breast cancer. However, ZFAS1 has been suggested to be overexpressed in most types of human cancers such as lung cancer [ 19 ], hepatocellular carcinoma [ 20 ], osteosarcoma [ 21 ], glioma [ 22 , 23 ], colorectal cancer [ 24–26 ], gastric cancer [ 27–29 ], esophageal squamous cell carcinoma [ 30 ], ovarian cancer [ 31 ], prostate cancer [ 32 ], and acute myeloid leukemia [ 33 ]. However, the expression status of ZFAS1 in bladder cancer was still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by He et al [45], Smad7 down-regulation could promote TGF-β1-mediated cardiac fibrosis, which is one of the major mechanisms of cardiac fibrosis. Liu et al also reported that osthol treatment could alleviate TGF-β1-induced cardiac fibrosis with increased Smad7 expression and reduced collagen I/III ratios and α-SMA and ECM deposition [46]. Importantly, He et al [47] found that miR-21 could down-regulate Smad 7 to enhance TGF-β1/Smad signaling and promote AF-induced cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the dysregulation of lncRNAs ATB [ 51 ], XIST [ 74 ], AK001796 [ 93 ], MALAT1 [ 147 ], nuclear transcription factor NF-κB interacting lncRNA (NKILA) [ 162 ], SPRY4-IT1 [ 163 ], and zinc finger antisense 1 (ZFAS1) [ 164 ] has also been demonstrated to be markedly associated with advanced lymph node metastasis, aggressive TNM stage, and shorter survival time. These lncRNAs may also serve as potential prognostic biomarkers for EC.…”
Section: Tumor Prognosismentioning
confidence: 99%